Jak poznaniacy oceniają obecność germanizmów w swojej gwarze? - Piotrowicz, Anna; Witaszek-Samborska, Małgorzata (Slavia Occidentalis, 2015)
The article presented and interpreted results of the survey. More precisely – the answers given by respondents three questions, which were: “What do you think about the presence of German loanwords in the Poznań dialect? Is it a lot of them? Are they still alive?”. The survey covered 120 people from Poznań (and Wielkopolska, but at least 20 years of living in the city), representing three age groups. It turned out that most of the inhabitants of Poznań has a positive attitude towards the German loanwords present in their dialect. They note their recessive character of the cross-generational. They admit, however – and this regardless of age – that there are still a lot. Most of the respondents are aware of the limitations of pragmatic and communication accompanying the use of regional German loanwords. Today the influence German into Polish no longer raises such negative connotations as before, so the evaluation of regional German loanwords is more objective.